IMPROVING THE INVESTMENT CLIMATE IN UZBEKISTAN — AN IMPORTANT FACTOR OF ECONOMIC DEVELOPMENT - Sharafuddinova Madina Isomuddin qizi (Ecomind Press, 2026)
This article examines the importance of improving the investment climate in Uzbekistan for economic development. The investment climate is considered a key condition for the sustainable growth of the national economy, modernization of industries, and enhancement of product competitiveness. The article analyzes the conditions for attracting foreign and domestic investments into the national economy, ways to increase their effectiveness, as well as mechanisms for strengthening the attractiveness of the investment climate. The results of the study contribute to the development of practical recommendations for promoting investment activity and ensuring economic growth.
Keywords: This article examines the importance of improving the investment climate in Uzbekistan for economic development. The investment climate is considered a key condition for the sustainable growth of the national economy, modernization of industries, and enhancement of product competitiveness. The article analyzes the conditions for attracting foreign and domestic investments into the national economy, ways to increase their effectiveness, as well as mechanisms for strengthening the attractiveness of the investment climate. The results of the study contribute to the development of practical recommendations for promoting investment activity and ensuring economic growth.